2021
DOI: 10.3390/jpm11080799
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic Gap as a Useful Surrogate Marker for Glucose Variability and Progression of Diabetic Retinopathy

Abstract: (1) Background: Recent studies have reported that the glucose variability (GV), irrespective of glycosylated hemoglobin (HbA1c), could be an additional risk factor for the development of diabetic retinopathy (DR). However, measurements for GV, such as continuous glucose monitoring (CGM) and fasting plasma glucose (FPG) variability, are expensive and time consuming. (2) Methods: This present study aims to explore the correlation between the glycemic gap as a measurement of GV, and DR. In total, 2565 patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Earlier studies revealed that glycated hemoglobin ( 10 , 11 , 13 , 15 17 , 19 ) or glycemic variability ( 20 , 21 ) could be predictors for DR, but structured glycemic detection adherence was highly correlated with social support ( 24 ). Local experience-based studies from China, India, and Brazil have indicated that the routine use of SMBG was frequently challenging, mainly because of the out-of-pocket expenditures associated with glucose monitoring ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Earlier studies revealed that glycated hemoglobin ( 10 , 11 , 13 , 15 17 , 19 ) or glycemic variability ( 20 , 21 ) could be predictors for DR, but structured glycemic detection adherence was highly correlated with social support ( 24 ). Local experience-based studies from China, India, and Brazil have indicated that the routine use of SMBG was frequently challenging, mainly because of the out-of-pocket expenditures associated with glucose monitoring ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several molecular and biochemical pathways are involved in the incidence and development of DR, but the interactions between various mechanisms remain to be fully elucidated ( 9 ). Clinical studies have identified a number of risk factors for DR, including demographic characteristics such as age ( 10 12 ), duration of diabetes ( 10 , 11 , 13 17 ), obesity ( 10 ), and pregnancy status in diabetic women of childbearing age ( 18 ), comorbidities or complications such as hypertension ( 10 , 12 , 16 ), dyslipidemia ( 10 , 12 , 13 ), cardiovascular disease(CVD) ( 11 , 12 ) and diabetic nephropathy ( 10 , 12 , 17 , 19 ), and other laboratory parameters such as glycated hemoglobin ( 10 , 11 , 13 , 15 17 , 19 ), glycemic variability ( 20 , 21 ), and susceptibility genes ( 22 ). However, the aforementioned risk factors derived from population-based studies can only account for 9% of DR progression ( 23 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The diagnostic criteria for SIH were as follows: (1) no previous history of diabetes, (2) admission FBG ≥ 7 mmol/L, and (3) normal HbA1c values [ 28 ]. The effect of long-term glycemic control on hyperglycemia can be excluded from the calculation of GG in diabetic patients, and GG could be a simple measurement for glucose variability [ 28 , 29 , 30 ]. GG was calculated as preoperative FBG minus the HbA1c-derived average glucose level [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…Hsing et al investigated the possibility of using the glycemic gap as a surrogate for glucose variability. Findings suggest that a negative glycemic gap is associated with progression and show the importance of minimizing glucose fluctuations [10].…”
Section: Systemic Biomarkersmentioning
confidence: 97%